PENGADAAN TANAH DALAM PEMBANGUNAN INFRASTRUKTUR JALAN TOL OLEH BADAN USAHA MILIK NEGARA (PERSERO) - Evi Fajriantina Lova (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2016)
AbstractIn the construction of highway infrastructure prevailing land acquisition for public use, is based on Article 10 (b) of Law No. 2 of 2012. Looking at the status of State-Owned Enterprises is a Persero, whether the land acquisition is in conformity with the qualification of the public interest. The purpose of this paper is to investigate and analyze whether in the procurement of land for development in the public interest SOE (Persero) meets the principles of public interest. What are the barriers and efforts in the implementation of land acquisition for the construction of highway infrastructure. And how the principle of fairness in compensation in land acquisition for the construction of highway infrastructure. The research method in this study is normative and empirical jurisdiction. The approach used is the approach of legislation, conceptual and qualitative. Based on this research, land acquisition in the construction of highway infrastructure by State Owned Enterprises (Persero) already meets the principles of public interest, namely the construction is actually owned by the government, by the government and non-profit so it can be qualified as land acquisition for public purposes , Bottlenecks in the procurement of land for the construction of highway infrastructure, among others: Judging from the substance of the law, there are many rules are unclear so in practice lead to injustice in society. Judging from the performance of its legal structure of the Land Acquisition Committee is less serious that a lot of dissatisfaction in the society, especially in terms of determining the value of compensation deliberations. Judging from its legal culture, the development of individualistic values â€‹â€‹in society as a barrier to the determination of compensation. As well as the principle of fairness in compensation on land acquisition in toll road infrastructure development can not be achieved. Key words: land acquisition, toll roads, state enterprises, state-owned Abstrak Dalam pembangunan infrastruktur jalan tol berlaku pengadaan tanah untuk kepentingan umum, ini berdasarkan Pasal 10 (b) Undang-Undang Nomor 2 Tahun 2012. Melihat status dari Badan Usaha Milik Negara adalah Persero, apakah pengadaan tanah tersebut sudah sesuai dengan kualifikasi kepentingan umum. Tujuan dari penulisan jurnal ini adalah untuk mengetahui dan menganalisis apakah dalam melakukan pengadaan tanah bagi pembangunan untuk kepentingan umum BUMN (Persero) sudah memenuhi prinsip-prinsip kepentingan umum. Apa saja hambatan dan upaya dalam pelaksanaan pengadaan tanah untuk pembangunan infrastruktur jalan tol. Serta bagaimana prinsip keadilan pada pemberian ganti rugi dalam pengadaan tanah untuk pembangunan infrastruktur jalan tol. Metode penelitian dalam penelitian ini adalah yuridis normatif dan yuridis empiris. Pendekatan yang digunakan adalah pendekatan undang-undang, konseptual dan kualitatif. Berdasarkan hasil penelitian, Pengadaan tanah dalam pembangunan infrastruktur jalan tol oleh Badan Usaha Milik Negara (Persero) sudah memenuhi prinsip kepentingan umum yaitu pembangunan tersebut benar-benar dimiliki oleh pemerintah,Â dilakukan oleh pemerintah dan tidak mencari keuntungan sehingga dapat dikualifikasikan sebagai pengadaan tanah untuk kepentingan umum. Hambatan dalam pelaksanaan pengadaan tanah untuk pembangunan infrastruktur jalan tol antara lain: Dilihat dari substansi hukumnya, masih banyak aturan yang belum jelas sehingga dalam prakteknya menimbulkan ketidakadilan dalam masyarakat. Dilihat dari struktur hukumnya kinerja Panitia Pengadaan Tanah kurang serius sehingga banyak ketidakpuasan dalam masyarakat, terutama dalam hal musyawarah penentuan nilai ganti rugi. Dilihat dari budaya hukumnya, berkembangnya nilai individualistik dalam masyarakat menjadi penghambat dalam penentuan pemberian ganti rugi. Serta prinsip keadilan dalam pemberian ganti rugi pada pengadaan tanah dalam pembangunan infrastruktur jalan tol belum dapat tercapai. Kata kunci: pengadaan tanah, jalan tol, BUMN, persero